2016
DOI: 10.2147/opth.s95212
|View full text |Cite
|
Sign up to set email alerts
|

Associated depression in pseudophakic patients with intraocular lens with and without chromophore

Abstract: BackgroundWith aging, the crystalline lens turns yellowish, which increases the absorption of wavelengths in the blue electromagnetic spectrum, reducing their photoreception in the retina. Since these wavelengths are the main stimulus in the regulation of the circadian rhythm, progressive reduction in their transmission is associated with chronic sleep disturbances and depression in elderly patients. Cataract extraction improves circadian photoreception at any age. However, lenses that block blue waves have 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…In contrast, more recent studies note that the biological effects of cataract surgery may be dependent upon the transmission properties of IOL. Older patients receiving conventional IOL exhibited improved cognitive function and increased slow-wave sleep ( Chellappa et al., 2019 ) and reduced parameters of depression ( Mendoza-Mendieta and Lorenzo-Mejia, 2016 ) and mood disorders ( Zambrowski et al., 2018 ) compared with those implanted with BF-IOL ( Ayaki et al., 2015 ). In a randomized study comparing the long-term effects of type of IOL, the only durable difference was that blue blocking IOLs increased sleep efficiency ( Brondsted et al., 2015 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, more recent studies note that the biological effects of cataract surgery may be dependent upon the transmission properties of IOL. Older patients receiving conventional IOL exhibited improved cognitive function and increased slow-wave sleep ( Chellappa et al., 2019 ) and reduced parameters of depression ( Mendoza-Mendieta and Lorenzo-Mejia, 2016 ) and mood disorders ( Zambrowski et al., 2018 ) compared with those implanted with BF-IOL ( Ayaki et al., 2015 ). In a randomized study comparing the long-term effects of type of IOL, the only durable difference was that blue blocking IOLs increased sleep efficiency ( Brondsted et al., 2015 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of various studies of the use of blue-filtering IOLs suggest that they do not provide protection to the retina, and in addition, they have certain disadvantages in terms of their affecting the quality of vision, especially in mesopic and/or scotopic conditions [46]. In addition, they have been linked with changes to circadian rhythms [26, 47] and depression [25]. However, other authors have demonstrated the protective capacity of blue-filtering IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors indicate that using UV/blue-filtering IOLs causes quality of vision impairment [23] or have not detected protective effects after implantation [24]. Conversely, other authors report that the use of UV/blue-filtering IOLs was useful in retinal protection [25]. Here, we show the first in vitro study analyzing a large number of IOL models in a controlled environment to elucidate the erratic effect of the use of UV/blue-filtering IOLs.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults need more light than younger ones for the same ocular transmittance because of age-related pupillary miosis, progressive photoreceptor loss, and the indoor illumination lifestyle of many elderly individuals [29,54,343,354,355]. The potential health benefits of cataract surgery's improvement of blue light-dependent retinal ganglion photoreception were identified over a decade ago [54,354,355] and confirmed in more recent studies on pseudophakic depression [356], longevity [357], cognition [358,359], and sleep [359,360].…”
Section: Age-related Macular Degeneration and Intraocular Lensesmentioning
confidence: 99%